The interchangeability of two assays for the measurement of anti-Müllerian hormone when personalizing the dose of FSH in in-vitro fertilization cycles. (3rd April 2021) - La Marca, Antonio; Tolani, Aarti Deenadayal; Capuzzo, Martina
Abstract: Objective: Study the interchangeability of Roche Elecsys and Beckman Coulter Access anti-Müllerian Hormone (AMH) assays to select the gonadotropin starting dose in IVF cycles. Methods: Patients' AMH was measured using both Elecsys and Access automated assays. AMH values were then used to calculate the FSH starting dose. The main outcome is the percentage of women that would have been stratified to a different dose of gonadotropin due to differences in AMH values from the two tests. Results: The Access assay systematically gives higher values compared with the Elecsys assay (slope = 0.88). For Follitropin Alfa, the difference in starting dose was > 15% in 2/113 patients, when Access AMH was used instead of Elecsys. For Follitropin Delta the difference in the starting dose was >15% in 21/113 patients when using Access AMH. When considering women with high ovarian reserve, only 4/51 would have received a Follitropin Delta dose that exceeded a 15% difference using Access AMH as a substitute for the Elecsys value. Conclusions: The use of the Roche Elecsys or Beckman Coulter Access leads to modest differences in AMH values, which seem to little affect the calibration of FSH dose used for ovarian stimulation.